A few good men - Reiner, Rob; Columbia Pictures; Castle Rock Entertainment (Firm) (Culver City, California : Columbia TriStar Home Video, 1999)
Cruise stars as a brash Navy lawyer who's teamed with a gung-ho litigator in a politically-explosive murder case. Charged with defending two Marines accused of killing a fellow soldier, they are confronted with complex issues of loyalty and honor - including its most sacred code and its most formidable warrior
Cast : Tom Cruise, Jack Nicholson, Demi Moore
Keywords: Trials (Murder) -- United States -- Drama; Defense (Criminal procedure) -- United States -- Drama; Military law -- United States -- Drama; Feature films